2011
DOI: 10.1002/cbic.201100579
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution Strategies for Enantiocomplementary Haloalkane Dehalogenases: From Chemical Waste to Enantiopure Building Blocks

Abstract: We used directed evolution to obtain enantiocomplementary haloalkane dehalogenase variants that convert the toxic waste compound 1,2,3-trichloropropane (TCP) into highly enantioenriched (R)- or (S)-2,3-dichloropropan-1-ol, which can easily be converted into optically active epichlorohydrins-attractive intermediates for the synthesis of enantiopure fine chemicals. A dehalogenase with improved catalytic activity but very low enantioselectivity was used as the starting point. A strategy that made optimal use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 105 publications
0
35
0
3
Order By: Relevance
“…This enzyme is able to convert 1,2,3-trichloropropane (TCP) into ( R )- or ( S )-2,3-dichloropropan-1-ol, which can be converted into optically active epichlorohydrins, industrially important building blocks for the synthesis of fine chemicals. Enatioselectivity of the WT DhaA was further improved [120] by a pair-wise SSM approach applied to 16 active-site residues not directly involved in the catalytic reaction. A further refinement was then applied to the best R- and S-enantioselective variants by site directed mutagenesis including residues that are not part of the active site.…”
Section: Recent Successful Applicationsmentioning
confidence: 99%
“…This enzyme is able to convert 1,2,3-trichloropropane (TCP) into ( R )- or ( S )-2,3-dichloropropan-1-ol, which can be converted into optically active epichlorohydrins, industrially important building blocks for the synthesis of fine chemicals. Enatioselectivity of the WT DhaA was further improved [120] by a pair-wise SSM approach applied to 16 active-site residues not directly involved in the catalytic reaction. A further refinement was then applied to the best R- and S-enantioselective variants by site directed mutagenesis including residues that are not part of the active site.…”
Section: Recent Successful Applicationsmentioning
confidence: 99%
“…The hydrolytic reaction turns (mostly toxic) halogenated alkanes to the corresponding, non-hazardous alcohols. The need for new haloalkane dehalogenases or the engineering of characterized enzymes is high as they are useful for, e.g., detoxification of halide compounds (Bosma et al 2002) or the production of enantiopure fine chemicals (Prokop et al 2010;van Leeuwen et al 2012). The first described haloalkane dehalogenase was in 1985 the DhlA from Xanthobacter autotrophicus GJ10, which is able to hydrolyse 1,2-dichloroethane (Keuning et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of easy to use highthroughput assays turned out to be a major hindrance as screening for active or enantioselective haloalkane dehalogenase variants could only be achieved with low throughput using a pH assay (Holloway et al 1997) or gas chromatographic (GC) analysis (van Leeuwen et al 2012). For the pH assay, the proton released during the reaction causes a pH shift indicated by phenol red, with the disadvantage of only a modest sensitivity and the drawback that often false-positive variants are detected, especially when crude cell lysate is used.…”
Section: Introductionmentioning
confidence: 99%
“…Although kinetic resolution has a maximum yield of 50%, both enantiomers could be obtained by the resolution of a racemic mixture using enantiocomplementary enzymes (21,22). Directed evolution of enantiocomplementary enzymes has been investigated recently for the production of several optically active compounds (8,9,23). Wu et al reported the evolution of enantiocomplementary Candida antarctica lipase B mutants for the hydrolytic kinetic resolution of p-nitro-phenyl-2-phenylpropanoate by applying iterative saturation mutagenesis (ISM) (9).…”
mentioning
confidence: 99%
“…Wu et al reported the evolution of enantiocomplementary Candida antarctica lipase B mutants for the hydrolytic kinetic resolution of p-nitro-phenyl-2-phenylpropanoate by applying iterative saturation mutagenesis (ISM) (9). In conjunction with the strategies for constructing high-quality libraries, van Leeuwen et al also adopted the ISM strategy to obtain enantiocomplementary haloalkane dehalogenase variants that catalyze the conversion of 1,2,3-trichloropropane to enantiopure building blocks (23). These results indicated that the active-site residues are indeed hot spots for manipulating enzyme enantioselectivity, although the high risk of inactivation could not be excluded.…”
mentioning
confidence: 99%